Closing the gap between rhetoric and practice in strengths‐based approaches to Indigenous public health: a qualitative study. (8th January 2020) - Askew, Deborah A.; Brady, Karla; Mukandi, Bryan; Singh, David; Sinha, Tanya; Brough, Mark; Bond, Chelsea J.
Abstract: Objective : To understand strengths‐based practice as articulated by urban Indigenous community workers and to consider its application for public health approaches to Australian Indigenous health advancement. Methods : Semi‐structured interviews with community workers from an urban Indigenous community. Interviews were video and audio recorded and transcribed verbatim. Data were analysed using thematic analysis, using an Indigenist research framework. Results : For our participants (11 Indigenous and one non‐Indigenous), a strengths‐based approach was fundamental to their practice. This approach reconfigured the usual relationship of client and service provider to fellow community member. They understood the strength of Indigeneity that empowers individuals and communities. They were not blinkered to the challenges in the community but resisted defining themselves, their community or their community practice by these deficits. Conclusions : Our participants had a sophisticated experiential understanding that a strengths‐based practice is not simply a 'culturally acceptable' way for non‐Indigenous peoples to work for Indigenous peoples, but rather it is the only way of working with Indigenous people. Implications for public health : Strengths‐based practice requires a reconfiguring of relationships of power, of attending to structure over stereotypes, and privileging Indigenous ways of knowing, being and doing. This reconfiguration is an ethical prerequisite for an approach that is genuinely strengths‐based.